A systematic, updated review of Xuezhikang, a domestically developed lipid-lowering drug, in the application of cardiovascular diseases - Cheng Yang; Yongjian Wu; Jie Qian; Jian-Jun Li (Acta Pharmaceutica Sinica B)
Cardiovascular diseases (CVDs) are a major threat to public health globally. A large proportion of people with dyslipidaemia have poorly controlled lipid levels, emphasizing the need for alternative lipid-lowering treatments that are both effective and safe. Xuezhikang, a red yeast rice (RYR) extract, containing 13 kinds of monacolins and other bioactive components, emerges as one such promising option. Its discovery was built on a long history of RYR use as a functional food supplement and traditional Chinese medicine. Several randomized, controlled clinical trials have substantiated its lipid-lowering effects and its potential to protect against CVDs. Safety concerns with statins did not arise during decades of experience with Xuezhikang treatment in clinical practice. The approval of Xuezhikang in multiple regions of Asia marked a conceptual shift in CVD management, moving from single agents to polypills and from synthetic medicines to natural extracts. This review comprehensively addresses important topics related to this medicinal natural extract, including the ancient utilization of RYR, the development of Xuezhikang, its mechanisms of action, pleiotropic effects, clinical studies, challenges, and future perspectives to enhance our understanding regarding the role of Xuezhikang, a representative, domestic lipid-lowering drug of RYR, in prevention and treatment of CVD.